2017
DOI: 10.1038/s41598-017-13001-2
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of marine mercury to mountain lakes

Abstract: Stocking is a worldwide activity on geographical and historical scales. The rate of non-native fish introductions have more than doubled over the last decades yet the effect on natural ecosystems, in the scope of biologically mediated transport and biomagnification of Hg and Hg-isotopes, is unknown. Using geochemistry (THg) and stable isotopes (N, Sr and Hg), we evaluate natal origin and trophic position of brown trout (Salmo trutta fario), as well as mercury biomagnification trends and potential pollution sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
3
9
0
Order By: Relevance
“…The relatively higher value of Hg concentrations and Hg accumulation rates in this population dovetail remarkably well with processes that have recently been described in highaltitude aquatic ecosystems (Hansson et al, 2017). In this study system, farmed trout raised on commercial pellets based on proteins from fishery products of marine origin show both high Hg concentrations and Hg isotopic signatures that are comparable to that of top-predator marine biota (Hansson et al, 2017). It is likely that the commercial pellets used to raise trouts at the Fontenille fish farm are also based on proteins from fishery products of marine origin, and that introduction of marine Hg through the fish food is responsible for the higher value of Hg concentrations and Hg accumulation rates in this N. maura population.…”
Section: Speciessupporting
confidence: 85%
See 2 more Smart Citations
“…The relatively higher value of Hg concentrations and Hg accumulation rates in this population dovetail remarkably well with processes that have recently been described in highaltitude aquatic ecosystems (Hansson et al, 2017). In this study system, farmed trout raised on commercial pellets based on proteins from fishery products of marine origin show both high Hg concentrations and Hg isotopic signatures that are comparable to that of top-predator marine biota (Hansson et al, 2017). It is likely that the commercial pellets used to raise trouts at the Fontenille fish farm are also based on proteins from fishery products of marine origin, and that introduction of marine Hg through the fish food is responsible for the higher value of Hg concentrations and Hg accumulation rates in this N. maura population.…”
Section: Speciessupporting
confidence: 85%
“…This study site is situated on a fish farm, and N. maura from this population feed heavily on the fry and juveniles trouts raised by the fish farm. The relatively higher value of Hg concentrations and Hg accumulation rates in this population dovetail remarkably well with processes that have recently been described in highaltitude aquatic ecosystems (Hansson et al, 2017). In this study system, farmed trout raised on commercial pellets based on proteins from fishery products of marine origin show both high Hg concentrations and Hg isotopic signatures that are comparable to that of top-predator marine biota (Hansson et al, 2017).…”
Section: Speciessupporting
confidence: 84%
See 1 more Smart Citation
“…Alternatively, relatively high concentrations of both Hg and Zn could be linked to the composition of fish pellets used for fish farming that occur in many ponds of Brenne. Indeed, commercial fish pellets exhibit high Hg concentrations of marine origin (Hansson et al 2017; see also Lemaire et al 2018) and are enriched with Zn oxide (EFSA 2012). Future studies should usefully investigate both the origin of Hg and Zn as well as the physiological and toxicological consequences of elevated levels of these elements for E. orbicularis (Meyer et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Cryptic sources can further complicate our understanding of the extent of Hg contamination. For instance, it has recently been shown that fish farming is responsible for the transfer of marine Hg to areas that superficially appear unaffected from other sources of pollution (Hansson et al 2017; see also Lemaire et al 2018;Guillot et al 2018).…”
Section: Introductionmentioning
confidence: 99%